Standards of Excellence for Public Administration Education (African Journal of Public Administration & Management, 2026)
The SoE are a set of criteria that defines the highest quality & performance level in education & training programs related to public administration. These Standards guide academic & training institutions, trainers, & practitioners who aim to promote quality education. Applying these Standards of Excellence in public administration education & training programs will result in more dynamic, tech-savvy, agile & globally aware public servants & professionals who can navigate an ever-changing landscape & contribute to the advancement of sustainable development.